The Effects of Counterpressure and Effleurage Techniques on Pain and Anxiety Among Women in The Active Phase of The First Stage of Labor - Handayani, Tri Lestari; Rahayu, Novita Hesti; Rakhmawati , Nur Endah (Journal of Health Empowerment and Interprofessional Practice, 2026)
Background: Labor pain and anxiety commonly occur during the active phase of the first stage of labor and may negatively affect maternal comfort and labor progress. This study aimed to compare the effectiveness of counterpressure and effleurage techniques in reducing pain and anxiety among women in labor.Methods: A quasi-experimental comparative design was applied involving 36 women in the active phase of the first stage of labor at Hermina Banyumanik Hospital, Semarang. Participants were divided into counterpressure and effleurage intervention groups. Pain intensity was measured using the Numerical Rating Scale (NRS), and anxiety was assessed using the Visual Analog Scale for Anxiety (VAS-A). Data were analyzed using paired and independent t-tests.Results: Both counterpressure and effleurage significantly reduced pain and anxiety levels (p < 0.05). Effleurage showed a greater reduction in pain compared to counterpressure, while no significant difference was found between the two techniques in reducing anxiety.Conclusion: Counterpressure and effleurage are effective non-pharmacological interventions for reducing pain and anxiety during labor. Effleurage may be more effective for pain reduction.